A statistical and post-mortem study of wear and performance of MgO-C resin bonded refractories used on the slag line ladle of a basic oxygen steelmaking plant. (August 2017) - Borges, Ronaldo Adriano Alvarenga; Lenz e Silva, Guilherme Frederico Bernardo
Abstract: Refractories are essential materials used in steelmaking equipment. Understanding their wear mechanisms is important to promote safe, low-cost and high-performance steel processing. In the present work, a wear and performance evaluation of MgO-C refractories from steelmaking ladles was performed using statistical and post-mortem analyses to identify the main causes of degradation and failure. The post-mortem analysis showed that the main wear mechanism involved in the degradation process was the chemical corrosion of magnesia grains facilitated by the addition of nepheline fluxing, which is linked to the production method of steel grades with low sulfur content. Chemical corrosion of magnesia grains in the refractories used for ladle slag lines was intensified by the sodium-rich calcium-aluminum silicate slag reactions that dissolve magnesium, decreasing life of the equipment. A statistical evaluation of steelmaking shop ladles during 2015 (approximately 6700 heats) showed the main cause of degradation of the refractory ladle to be totally linked to the manufacturing process of low-grade sulfur steels. Highlights: The main wear phenomena involved on MgO-C refractories was chemical corrosion. Chemical corrosion of magnesia grains is facilitated by the nepheline addition. Ladle life degradation is linked to the low grade sulfur steels manufacturing. Refractories post-mortem of an industrial steelmaking ladle Statistical and correlation analysis about 6, 700 heats